Gaya Kepemimpinan Kepala Ruangan terhadap Penerapan Prinsip Etik Keperawatan dalam Pemberian Asuhan Keperawatan - Siska Ocfica Mariaty Napitupulu; Arlina Nurbaity Lubis; Etti Sudaryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to see the effect of the situational leadership style of the head of the room on the application of nursing ethical principles. This research method is quantitative research with a correlation design. The results showed that the situational leadership style of the head of the room in the inpatient room that dominated more was consultation, namely 35 nurses (33.3%), and the principles of nursing ethics showed a suitable category, as many as 84 (80%). In conclusion, there is an influence of the situational leadership style of the head of the room on the application of nursing ethical principles in providing nursing care at the University Hospital of North Sumatra. Keywords: Leadership Style, Nursing Ethical Principles